Knowledge, attitudes, and experiences of a group of turkish dentists regarding child abuse = Conocimientos, actitudes y experiencias de un grupo de dentistas turcos en relación con el abuso infantil - Ceyhan, Derya (2023)
Child abuse is a universal problem with critical lifelong effects. This study aimed to evaluate knowledge, attitudes, experiences of dentists regarding child abuse and to increase relevant awareness of them. A self-administered questionnaire with 48 questions about dentists' personal and educational information and their level of knowledge, attitudes, experiences on child abuse was implemented. Out of targeted 305 participants, 183 (60.0%) returned completely filled out questionnaires. Majority of participants knew signs and symptoms of child abuse. Of the participants, more than half were well-informed on what to do, however, one quarter had no knowledge about where to report in case of child abuse. In identifying child abuse, 39.3% of the participants found themselves inadequate. The most commonly stated reason for low rate of reporting was hesitancy to identify the case as abuse, and all participants needed more training. Only 12 (6.6%) participants suspected a case of child abuse. Dentists who had children and were long-time experienced and generalist did not have sufficient knowledge about legal obligations, signs and symptoms of child abuse (p<0.05). Arrangements and training programs to increase knowledge, awareness, and responsibility levels of dentists about child abuse appear to be a critically important topic.
El abuso infantil es un problema universal con efectos críticos de por vida. Este estudio tuvo como objetivo evaluar el conocimiento, las actitudes y las experiencias de los dentistas con respecto el abuso infantil y aumentar la conciencia relevante sobre ellos. Se implementó un cuestionario autoadministrado con 48 preguntas sobre información personal y educativa de los odontólogos y su nivel de conocimientos, actitudes, experiencias sobre el abuso infantil. De los 305 participantes seleccionados, 183 (60.0%) devolvieron los cuestionarios completos. La mayoría de los participantes conocían los signos y síntomas del abuso infantil. De los participantes, más de la mitad estaban bien informados sobre qué hacer, sin embargo, una cuarta parte no sabía dónde denunciar en caso de abuso infantil. Al identificar el abuso infantil, el 39.3% de los participantes se encontraron inadecuados. La razón más común para la baja tasa de informes fue la vacilación para identificar el caso como abuso, y todos los participantes necesitaban más capacitación. Solo 12 (6.6%) participantes sospecharon un caso de abuso infantil. Los odontólogos que tenían hijos y eran de larga experiencia y generalistas no tenían suficiente conocimiento sobre las obligaciones legales, signos y síntomas de abuso infantil (p<0,05). Los arreglos y los programas de capacitación para aumentar los niveles de conocimiento, conciencia y responsabilidad de los dentistas sobre el abuso infantil parecen ser un tema de importancia crítica.
En revista Odóvtos, vol. 25, no.1 (enero-abril 2023)
Descripción basada en el contenido visto el 13 de diciembre, 2024
También disponible en formato HTML y EPUB